IMPLEMENTATION OF SCIENCE AND TECHNOLOGY IN FEED PRODUCTION TOWARDS SELF-SUPPORTING CATFISH LIVESTOCK - Mastauli Siregar; Elita Dewi (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Feed is the main key to success in small and large scale catfish farming. If we keep catfish in a large scale, we must be smart to make feed management, of course. It is undeniable that many catfish farmers failed and went bankrupt because they did not know the correct technicalities in catfish farming. Where production costs in catfish cultivation are almost 70% in feed management. One alternative that can be done to reduce production costs is to make homemade feed through simple techniques by utilizing local sources of raw materials (including the utilization of agricultural industrial waste) which is relatively cheap. In addition to meeting their own needs, the artificial feed produced can also be sold to markets / other fish farmers so that it can provide multiple benefits. It is not an easy matter indeed to make fish feed itself, it requires special skills to be able to practice it themselves. Farmers must understand what content must be contained in the fish feed. In connection with this, it is deemed necessary to provide training in making their own catfish feed through simple techniques. It is also necessary to provide guidance and training that enables partners to calculate total sales revenue and total costs so that they are able to find out how much profit is earned per month. It is expected that after mentoring, partners will become more knowledgeable and able to apply it in their daily work. Thus partners will be more developed, become more economically independent, increase income, become more productive and become more optimistic in their efforts so that the entrepreneurial spirit is built.